New Own Resources for the EU Budget: Good Old Taxes Could also Do the Job - Traversa, Edoardo (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
The paper deals with issues related to currently discussed reform within the EU focused on the proposals of establishing the new own tax-based resources for the EU and the possibility to use an existing tax to transform it totally or partially into an EU tax based own resource which in his opinion seems to be the safest way forward from a legal perspective, as well as the future EU tax-based own resources.